Current tobacco use and its associated factors among adults in a country with comprehensive ban on tobacco: findings from the nationally representative STEPS survey, Bhutan, 2014. Issue 1 (December 2016) - Gurung, Mongal; Pelzom, Dorji; Dorji, Tandin; Drukpa, Wangchuk; Wangdi, Chador; Chinnakali, Palanivel; Goel, Sonu
Abstract Background Despite a comprehensive ban on cultivation, manufacture, distribution, and sale of tobacco products since 2004, two nationwide surveys conducted in 2012 and 2013 reported high tobacco use in Bhutan. National Health Survey 2012 reported that 4 % of the population aged 15–75 years used smoked tobacco and about 48 % used smokeless tobacco. Similarly, Global Youth Tobacco Survey (GYTS) of Bhutan reported tobacco use prevalence of 30.3 % in 2013. However, factors associated with this high tobacco use were not systematically studied. Hence, we assessed the prevalence of tobacco use and its associated sociodemographic, behavioral, and environmental factors. Methods This cross-sectional analytical study used secondary data collected in a nationally representative Non-communicable Disease Risk Factors Surveillance STEPS Survey 2014 conducted among Bhutanese adults (18–69 years). The survey included a total of 2820 adults; selected using multistage stratified cluster sampling. Weighted analysis was done to calculate the prevalence of tobacco use. Unadjusted and adjusted prevalence ratios were calculated using log binomial regression. Results The prevalence of current overall tobacco use was 24.8 % (95 % CI: 21.4–28.3) and that of smoked, smokeless, and dual forms (smoked and smokeless forms) were 7.4 % (95 % CI: 5.8–9.0), 19.7 % (95 % CI: 16.5–22.9), and 2.3 % (95 % CI: 1.8–2.9), respectively. Significantly higher prevalence of tobacco use in all forms was found among males, younger age groups, and alcohol users. The prevalence of smoked form was higher in urban areas compared to rural areas (11 % vs 6 %; aPR 1.8, 95 % CI: 1.5–2.0). Among individuals who reported having a non-communicable disease, the prevalence of smoked tobacco use was significantly lower than those who did not have disease (3.5 % vs. 8.3 %; aPR 0.5, 95 % CI: 0.3–0.9). Exposure to health warnings was protective for current tobacco use and smokeless tobacco use, while exposure to tobacco warnings through the media was helpful among smokers and overall tobacco users. Conclusions Despite a comprehensive ban on tobacco, tobacco use was high in Bhutan, especially the smokeless form. Males, younger age groups, and alcohol users should be targeted with behavioral interventions along the stricter implementation of tobacco control measures.